Enantioselectivity and mechanisms of chiral herbicide biodegradation in hydroponic systems. (November 2022) - Sun, Zhuanzhuan; Dzakpasu, Mawuli; Zhang, Dongxian; Liu, Guochen; Wang, Zhenzhen; Qu, Miaowen; Chen, Rong; Wang, Xiaochang C.; Zheng, Yucong
Abstract: This study demonstrates the enantioselective removal dynamics and mechanisms of the chiral herbicide metolachlor in a hydroponic system of Phragmites australis . It presents the first work to elucidate plant-microbial driven enantioselective degradation processes of chiral chemicals. The results showed a degradation efficiency of up to 95.07 ± 2.81% in the hydroponic system driven by a notably high degradation rate constant of 0.086 d −1 . P. australis was demonstrated to rapidly increase the contribution of biodegradation pathways in the hydroponic system to 82.21 ± 4.81% within 4 d with an enantiomeric fraction (EF) drop to 0.26 ± 0.02 to favour the enantioselective degradation of S-Metolachlor (kS-Metolachlor = 0.568 d −1 and kR-Metolachlor = 0.147 d −1 ). Comparatively, the biodegradation pathways in the control constituted less than 25%, with an EF value of circa 0.5. However, the enantioselective biodegradation pathways exhibited complete reversal after about 4 d to favour R-Metolachlor. Plants promoted the degradation of R-Metolachlor, evidenced by an increase in EF to 0.59 ± 0.03. Nonetheless, metolachlor showed an inhibitory effect on plants reflected by the reduction of plant growth rate, chlorophyll content, and electron transport rate to −7.85 ± 1.52%, 1.33 ± 0.43 mg g −1, 4.03 ± 1.33 μmol (m 2 s) −1, respectively. However, rhizosphere microorganisms aided plants to catalyze excessive reactive oxygen species production by the antioxidant enzymes to protect plants from oxidative damage and restore their physiological activities. High-throughput analysis of microbial communities demonstrated the enrichment of Massilia (40.63%) and Pseudomonas (8.16%) in the initial stage to promote the rapid degradation of S-Metolachlor. By contrast, the proliferation of Brevundimonas (32.29%) and Pseudarthrobacter (11.03%) in the terminal stage was closely associated with the degradation of R-Metolachlor. Moreover, as symbiotic bacteria of plants, these bacteria aided plants protection from reactive oxygen damages and promoted the recovery of plant metabolic functions and photosynthesis. Overall, these results demonstrate biodegradation mediated by plant-microbe mechanisms as the main driver for the enantioselective degradation of metolachlor in hydroponic systems. Graphical abstract: Image 1 Highlights: Metolachlor shows stereoselective degradation characteristics in hydroponics. The stereoselective degradation of Metolachlor is reversible. Plants aid enrichment of Metolachlor-degrading microbes and removal of enantiomers. Rhizosphere microbes promote reactive oxygen damage recovery and growth of plants.